Potential Bark Cinnamomum burmanii in Regenerating Damaged Liver Cells of Mice (Mus musculus) Diabetes Mellitus Model - Ukratalo, Abdul M; Kaihena, Martha; Sirait, Dion P O; Pattimura, Nadira; Manery, Dodikrisno Ekaputra (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2023)
Diabetes mellitus is a chronic disease that can quickly increase the prevalence of complications in sufferers, such as liver damage. This study aims to examine the effect of methanol extract cinnamon bark (Cinnamomum burmanii Bl) in regenerating liver cell damage mice (Mus musculus) Diabetes Mellitus through the histological picture. 20 mice were divided into 5 groups which consisted of a negative control group, Positive control and a group of mice that were given methanol extract bark Cinnamomum burmannii dose of 125 mg/head/day, 250 mg/head/Day and 500 mg/head/day. In the positive control group and the group of mice that will be given extract streptozotocin injected dose of 0.2 ml and observed blood sugar levels if sugar levels have increased then given methanol extract bark Cinnamomum burmannii with a dose that has been determined and blood sugar levels were measured. On the last day, surgery is performed to remove the liver, after which histological preparations are made. The results showed that the administration of bark extract Cinnamomum burmanii can regenerate damaged liver cells of mice due to diabetes mellitus. This is due to the content of secondary metabolite compounds contained in the bark of Cinnamomum burmannii.